Comportamento mecânico e de flamabilidade de compósito de polipropileno reclicado com fibra de coco e hidróxido de alumínio - SILVA, Vera Lúcia Dias da (Universidade Federal do Pará, 2012)
The plastic recycling has been an interesting possibility to minimize the destiny problem of the plastic residues. The polypropylene (PP) is enters the types polymers of larger consumption, therefore the utilization of this material has been enabling the studies development of great scientific and social relevance. This polymer presents excellent cost-performance relation, besides can be easily conformed and to exibit mechanical properties that turns it useful in several applications. However, this material when being burnt generates products that act as combustible so that, for some uses, flame resistance good is necessary. This can be gotten by flame retardant addition, that has the intention to increase the resistance of this material to the ignition and, at the same time reducing the propagation speed of the flame. The aluminium hydroxide, or simply alumina hydrate, is the flame retardant agent used most in the market, therefore it also acts as smoke suppressant and it does not liberate toxic gases during the burning. However, for such properties, high alumina hydrate concentrations are necessary. This causes deterioration in the physical properties of the materials for not have reinforcing character. The natural fibres own good reinforcement capacity when combined adequately with polymers. Also presenting advantages as low cost, low density, biodegradability and in the combustion does not emanate toxic gases. In this work, mixtures contend alumina hydrate and coco fibres had been incorporated polypropylene with the objective of if finding an properties rocking adequate for use of this composite with characteristics flame resistance and mechanical performance. The composites were molded by hot compression and characterized by IV, DRX, MEV, mechanical and non-flammability tests. Increase in the elasticity modulus of the composites in general was observed, as well as increase in the tenacity resistance of the PP/coco fiber composite regarding pure PP. The results had indicated the efficiency of alumina hydrate as it flame retardant, in all the composites, except PP/F, classifying the materials as V-0 according to international norm UL 94V.